Experimental Investigation into Pull-Out Strength of Foamed Concrete Using Different Types of Screw - Mydin, M.A. Othuman; Noordin, N.; Matori, Z.; Sani, N. Md.; Zahari, N.F. (EDP Sciences, 2014)
This study focuses on the results of the comprehensive strength test to quantify the mechanical properties of the screw’s pullout strength on foamed concrete. Foamed concrete is classified as lightweight concrete that been produced by cement paste or mortar in which air-voids are entrapped in the mortar by a suitable foaming agent. These days, the use of foamed concrete has been recognized in the construction industry as wall blocks, wall panels and also material floor and roof screeds. Hence, the applications of this material should be maximized as it is multi-functional. As we know, the use of screws on the wall or ceiling is common in a building. The objective of this research is to examine and determine the pullout strength of various properties and types of screws in lightweight foamed concrete with various densities that may depict the best result of the pullout strength on foamed concrete. To visualize the different results of pullout strength, screws with and without wall plug will be used as well. The pullout strength will be tested using the Universal Testing Machine where it shall measure the ultimate load of the screws attached to the foamed concrete may resist.